A case of intra-operative anaphylactic shock in hepatic hydatidosis with inadequate chemotherapy and proximity to hepatic vessels - Noor Mohamed, Shawnas Bahnou; Newton, Mario Victor; Govindaraj, Sridar; Prakash, Clement; Pavithra, B.; Padaki, P. A.; Jasmine, A. (International Surgery Journal, 2018)
Incidence of intraoperative Hydatid anaphylaxis is 0.2-3.3% Reporting of such rare cases is crucial for future reference and study. 52 years old lady presented with hepatic hydatidosis. Computed Tomography showed 2 cystic lesions; one in segment 6, 7 in proximity to right hepatic vein; multiseptated cyst with multiple daughter cysts in segment 4 adjoining the middle hepatic vein with intracystic vessel. No rupture seen. Preoperatively she was prescribed Albendazole 400mg twice-daily for 3months. She was given Hydrocortisone before surgery. 10% povidone iodine mops to prevent intraperitoneal spillage and hypertonic saline used to flush the cyst. One hour after anesthesia when the Segment IV cyst close to middle hepatic vein was punctured she had anaphylactic shock, resuscitated. Marsupialization of both the cysts with omentoplasty and intracystic drains done. She recovered well and discharged with Albendazole for 1 month. Growing cyst produces complex echinococcal antigens, increased cellular immune response, Th2 balanced with Th1; elevated immunoglobulin levels. In dead cysts Th2 responses drop rapidly. Albendazole 10mg/kg for 3 months causes good cyst wall degeneration, less viability of protoscoleces and cyst, less echinococcal antigen production. After the surgery we found that she had stopped albendazole in the preoperative period, which she did not reveal pre-operatively fearing delay in surgery. Inadequate albendazole, close proximity of cysts to vascular structures with high intracystic pressure would have predisposed to develop anaphylactic shock during cyst handling. Preoperative Albendazole can reduce anaphylaxis, morbidity and mortality due to hydatid, making hydatid surgery safer.